2023
DOI: 10.31234/osf.io/6j9z5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural signals predict information sharing across cultures

Hang Yee Chan,
Christin Scholz,
Danielle Cosme
et al.

Abstract: Information sharing influences which messages spread and shape beliefs, behavior and culture. In a pre-registered neuroimaging study conducted in the US and the Netherlands we demonstrate replicability, generalizability, and predictive validity of a brain-based prediction model of information sharing. Replicating findings in Scholz et al (2017), Proc Natl Acad Sci 114, 2881–2886, self-, social- and value-related neural signals in a sample of individuals tracked the population sharing of US news articles. Pre-r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…In line with theoretical predictions (Berger, 2014;Falk & Scholz, 2018), we found that when people perceived content as more self and socially relevant, or the content elicited stronger activity in brain regions associated with self-referential processing and mentalizing, people reported stronger sharing intentions. Together with previous research examining specific self and social goals (Scholz et al, 2023), self-reported self and social relevance (Cosme et al, 2022), and activity in these brain systems (Baek et al, 2017a;Chan et al, 2023;Motoki et al, 2020;Scholz et al, 2017), these findings provide compelling correlational evidence that self-related and social motives encourage sharing.…”
Section: Neuropsychological Mechanisms Of Sharingsupporting
confidence: 70%
See 4 more Smart Citations
“…In line with theoretical predictions (Berger, 2014;Falk & Scholz, 2018), we found that when people perceived content as more self and socially relevant, or the content elicited stronger activity in brain regions associated with self-referential processing and mentalizing, people reported stronger sharing intentions. Together with previous research examining specific self and social goals (Scholz et al, 2023), self-reported self and social relevance (Cosme et al, 2022), and activity in these brain systems (Baek et al, 2017a;Chan et al, 2023;Motoki et al, 2020;Scholz et al, 2017), these findings provide compelling correlational evidence that self-related and social motives encourage sharing.…”
Section: Neuropsychological Mechanisms Of Sharingsupporting
confidence: 70%
“…These findings advance the value-based framework of sharing, which highlights selfrelated and social motives as two important sources of value when deciding whether or not to share (Scholz, Jovanova, et al, 2020;. Whereas previous studies testing this framework have been primarily correlational in nature (Baek et al, 2017a;Chan et al, 2023;Motoki et al, 2020;Scholz et al, 2017;Scholz, Jovanova, et al, 2020), this study adds critical causal evidence for the idea that self-related and social motives-here engaged through active reflection on the self and social relevance of information-drive sharing behavior and are supported by brain regions implicated in self-referential and social cognitive processes.…”
Section: Neuropsychological Mechanisms Of Sharingsupporting
confidence: 69%
See 3 more Smart Citations